Personality predicts the use of social information - Kurvers, Ralf H.J.M; van Oers, Kees; Nolet, Bart A; Jonker, Rudy M; van Wieren, Sipke E; Prins, Herbert H.T; Ydenberg, Ron C (Ecology letters, 2010)
Ecology Letters (2010) 13: 829-837 The use of social information is known to affect various important aspects of an individual's ecology, such as foraging, dispersal and space use and is generally assumed to be entirely flexible and context dependent. However, the potential link between personality differences and social information use has received little attention. In this study, we studied whether use of social information was related to personality, using barnacle geese, Branta leucopsis, where boldness is a personality trait known to be consistent over time. We found that the use of social information decreased with increasing boldness score of the individuals. Individuals had lower feeding times when they did not follow the social information and this effect was unrelated to boldness score. When manipulating social information, thereby making it incorrect, individuals irrespective of their boldness score, learned that it was incorrect and ignored it. Our results show that social information use depends on the personality type of an individual, which calls for incorporation of these personality-related differences in studies of spatial distribution of animals in which social information use plays a role.